Effect of COVID-19 pandemic on utilisation of community-based mental health care in North-East of Italy: A psychiatric case register study. (11th April 2023) - Prina, E.; Tedeschi, F.; Salazzari, D.; Botte, T.; Ballarin, M.; Rabbi, L.; Imperadore, G.; Roccato, S.; Nicolaou, S.; Ruggeri, M.; Gomez, F.; Lasalvia, A.; et al.
Abstract: Aims: WHO declared that mental health care should be considered one essential health service to be maintained during the coronavirus disease 2019 (COVID-19) pandemic. This study aims to describe the effect of lockdown and restrictions due to the COVID-19 pandemic in Italy on mental health services' utilisation, by considering psychiatric diagnoses and type of mental health contacts. Methods: The study was conducted in the Verona catchment area, located in the Veneto region (northeastern Italy). For each patient, mental health contacts were grouped into: (1) outpatient care, (2) social and supportive interventions, (3) rehabilitation interventions, (4) multi-professional assessments, (5) day care . A 'difference in differences' approach was used: difference in the number of contacts between 2019 and 2020 on the weeks of lockdown and intermediate restrictions was compared with the same difference in weeks of no or reduced restrictions, and such difference was interpreted as the effect of restrictions. Both a global regression on all contacts and separate regressions for each type of service were performed and Incidence Rate Ratios (IRRs) were calculated. Results: In 2020, a significant reduction in the number of patients who had mental health contacts was found, both overall and for most of the patients' characteristics considered (except for people aged 18–24 years for foreign-born population and for those with a diagnosis of schizophrenia. Moreover, in 2020 mental health contacts had a reduction of 57 096 (−33.9%) with respect to 2019; such difference remained significant across the various type of contacts considered, with rehabilitation interventions and day care showing the greatest reduction. Negative Binomial regressions displayed a statistically significant effect of lockdown, but not of intermediate restrictions, in terms of reduction in the number of contacts. The lockdown period was responsible of a 32.7% reduction (IRR 0.673; p -value <0.001) in the overall number of contacts. All type of mental health contacts showed a reduction ascribable to the lockdown, except social and supportive interventions. Conclusions: Despite the access to community mental health care during the pandemic was overall reduced, the mental health system in the Verona catchment area was able to maintain support for more vulnerable and severely ill patients, by providing continuity of care and day-by-day support through social and supportive interventions.